Leveraging Urban Environmental Technology for Adolescent Smoking Prevention: Development of the E-Nosmo Digital Application - Hadrianti Haji Darise Lasari; Rahmiati Rahmiati; Wahyuni Wahyuni; Ratna Setyaningrum; Fatma Sayekti Ruffaida; Framita Rahman; Arneta Meihua Inaya; Che Che Rinda Putri; Eva Meily Dwi Putri Wahyudi (Universitas Trisakti, 2026)
Smoking represents a commonly observed behavior across various segments of society. Despite widespread awareness of its harmful effects, the number of smokers continues to increase each year. In the ASEAN region, Indonesia has the highest smoking prevalence. In Banjar Regency, 15–19-year-olds make up the majority (51.35%) of new smokers. One of the main reasons teenagers start smoking is the process of social adjustment within their environment. Aim: This study aims to design an application to prevent smoking behavior among teenagers and to implement the E-Nosmo application at SMPN 1 Aranio, ensuring it aligns with its intended objectives. Methodology and results: The E-Nosmo application was developed using a specific design methodology, beginning with the conceptual design phase, including system architecture and prototype development. After approval, the application was developed and tested to ensure it achieved its goals. The results showed that 57% of students were at risk of engaging in smoking behavior, while 43% were not. The most significant contributing factor was social influence, particularly from family members and peers who smoke. Other contributing factors included family background, parental support, and economic conditions. Interestingly, cigarette advertising did not play a role in influencing students’ smoking behavior. To maintain student engagement, the application also includes interactive games. Conclusion, Significance, and Impact Study: One important recommendation for improving the application is to simplify the wording of the questions used to detect smoking behavior, as some students found them too complex to understand.